Selection Correction in Panel Data Models: An Application to Labour Supply and Wages - Christian Dustmann; María Engracia Rochina-Barrachina (Institute for the Study of Labor (IZA), 2000)
In recent years a number of panel estimators have been suggested for sample selection models, where both the selection equation and the equation of interest contain individual effects which are correlated with the explanatory variables. We review and compare some of these estimators, and apply them to estimating the return to actual labour market experience for females, using a panel of twelve years. All these estimators rely on the assumption of strict exogeneity of regressors in the equation of interest, conditional on individual specific effects and the selection mechanism. This assumption is likely to be violated in many applications. Also, life history variables are often measured with error in survey data sets, because they contain a retrospective component. We show how non-strict exogeneity and measurement error can be taken into account within the estimation methods discussed.
Keywords: C34; J3; C33; 330; Panel data sample selection estimators; female labour supply; estimation of wage equations; Panel; Mikroökonometrie; Statistisches Auswahlverfahren; Statistischer Fehler; Theorie; Schätzung; Frauenerwerbstätigkeit; Lohn; Humankapital; Deutschland; Berufserfahrung